Performance Development and Evaluation of Solar Air Collector with Novel Phase Change Material - V. Vedanarayanan; J. Dilli Srinivasan; K. Arulvendhan; P. Thirusenthil Kumaran; R. Selvakumar; T. Maridurai; M. Sudhakar; Sami Al Obaid; Saleh Alfarraj; M. M. Raj; Ishwarya Komalnu Raghavan (International Journal of Photoenergy)
Experiments were carried out on an evacuated tube solar air collector connected to intrinsic thermal power storage to provide warm air unless solar radiation was available. As a phase change material, stearic acid was employed (PCM). Water has been used as a base fluid for converting sunlight into electricity gain to warm air, and the solar collector’s manifold was connected to the intrinsic thermal energy store. The most significant temperature variation between warm air and ecologic air was 38°C and 22°C, respectively, during direct and indirect solar radiation. A circular fin arrangement was used to achieve a flow rate of 0.020 kg s-1. The efficiency of minimum airflow rates (0.020 kg s-1) was 0.08–0.48 times that of maximum airflow rates (0.04 kg s-1). Because of the PCM’s better heat-storing capability, this system has a benefit over sensible storage systems in that it may be used after sunset.